Evaluation of the stiffness modulus of bituminous mixtures using laboratory tests (NAT) validate by field back-analysis - Neves, J. (2005)
This paper concerns the evaluation of the stiffness modulus of bituminous mixtures by using the Nottingham Asphalt Tester (NAT). On the basis of indirect tensile laboratory test results, a practical model for stiffness modulus prediction in pavement bearing capacity analysis was established and calibrated for some typical bituminous mixtures used in Portuguese asphalt pavements. Validation of this model was based on two experimental fullscale pavements instrumented du ring construction. To study the bearing capacity of the pavement structure, wheel load tests were carried out with simultaneous instruments measurements. Experimental pavements response modelling during load tests was performed using the finite elements method. The reasonably agreements between the calculated and measured strains indicate that the stiffness modulus prediction method is greatly reliable for the bituminous mixtures tested and could be very useful for further bearing capacity design of asphalt pavements.